Farming with Predators - An agroecological approach to human-wildlife conflict on Namibian farmlands - Luyt, Eustatius du Chavoux (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDConsEcol)--Stellenbosch University, 2020.